The Rape of Dinah: Motives for Incorporation in the History of the Patriarchs - Klimova, Veronika (Verbum vitae, 2024)
This article presents a philological analysis of the tragic story of Dinah, the daughter of the patriarch Jacob, as described in Gen 34. A comprehensive analysis of the literary text in the context of the Bible as a whole reveals a number of contradictory elements within the narrative, which contribute to the heterogeneity and multi-layeredness of the biblical text. These elements indicate that the story underwent an earlier form and that the rape of Dinah was deliberately included in the narrative of the patriarchs. This article aims to elucidate the rationale behind the deliberate incorporation of Dinah’s rape into the history of the patriarchs. The following three motives are posited as the reasons for this incorporation: 1) the conquest of Shechem as the first city in the land of Canaan; 2) the explanation of the curse of Simeon and Levi; 3) the preservation of the integrity and purity of the nation.